EPISTEMIC AUTHORITY IN THE AGE OF ALGORITHMS: RECONFIGURING KNOWLEDGE LEGITIMACY IN ISLAMIC EDUCATION - Akhmadi Akhmadi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
The rapid expansion of algorithmic systems in education has begun to reshape not only how knowledge is accessed but how it is authorised. While existing scholarship examines artificial intelligence primarily in terms of pedagogy, efficiency, and governance, limited attention has been given to its impact on epistemic authority, particularly within religious educational traditions. This study investigates how algorithmic mediation reconfigures knowledge legitimacy in Islamic education. Employing a qualitative library-based methodology, the research engages interdisciplinary scholarship in sociology of knowledge, digital governance, and Islamic intellectual history to analyse the structural transformation of epistemic authority from relational transmission to computational visibility. The findings indicate that algorithmic systems function as epistemic intermediaries that influence credibility through ranking, optimisation, and generative synthesis. However, this shift does not displace traditional forms of authority grounded in textual continuity, moral exemplarity, and scholarly lineage. Instead, Islamic education now operates within a layered epistemic configuration in which relational, institutional, and algorithmic modalities of legitimacy coexist. The study proposes a layered epistemic model to conceptualise this coexistence and argues that epistemic authority in the age of algorithms must be understood as composite rather than singular. By extending debates on algorithmic governance into the domain of sacred knowledge traditions, this article contributes to broader discussions on educational legitimacy, digital transformation, and the future of epistemic authority in technologically mediated societies.